Pengembangan Modul Seni Musik Berbasis Experiential Learning untuk Meningkatkan Kemampuan Bermain Musik pada Mata Pelajaran Seni Budaya dan Prakarya Siswa Sekolah Dasar - Jaka Nugraha; Santoso -; Murtono - (el-Ibtidaiy:Journal of Primary Education, 2021)
The objectives of this study were (1) to analyze the needs of-based music modules experiential learning to improve the ability to play music in elementary school students, (2) to analyze the feasibility of the-based music art module module experiential learning to improve the ability to play music in elementary school students, (3) ) to analyze the effectiveness of the music art module based on experiential learning to improve the ability to play music in elementary school students. This research uses Research and Depelopment research methods referring to the 10 stages of Borg and Gall. Data collection used is the technique of observation, interviews, and performance of ability to play music. The analysis used in this research is quantitative and qualitative analysis, including the practice of musical instruments, learning observations, and validation of the musical arts module product. The product analysis of the musical arts module based on experiential learning to improve cultural arts and crafts in elementary schools includes 6 stages. Sources of data in this study were teachers and students of class VI SDN Magung 03 and SDN 04 Nagreg.  The results of the development of the musical arts module based on experiential learning contain the need for a special module which includes basic learning and the stages of learning in detail, therefore the development of a music art module based on experiential learning is made. After being validated by the validator, it gets a score of 87.5 with category valid. Then the-based music art module is experiential learning applied to the experimental class and the calculation results using the t test are obtained sig 5%, meaning that there is an increase in the ability to play music using the-based music art module experiential learning then the N-gain is 0.4 in the moderate category. The effectiveness test in this study was carried out by comparing the performance results of the student's ability to play music in the control class and the experimental class. It is found that tcount is 6.9. From the results of this study, it can be concluded that the musical arts module based on experiential learning can be used in learning cultural arts and crafts in high classes. Hopefully it can inspire teachers to innovate in other learning.